Old and new formulations of the neoclassical theory of aggregate investment: A critical review - Daniele Girardi (University of Massachusetts, Department of Economics, 2017)
This paper surveys the neoclassical theory of aggregate investment and its criticisms. We distinguish four main formulations of this theory: the traditional 'Wicksellian' investment function; the Fisherian 'array-of-opportunities' approach (as Witte Jr. called it); the Jorgensonian model; the now prevailing adjustment-costs models. With respect to other papers criticizing the neoclassical theory of investment, we do not appeal to market imperfections. We instead argue that all four formulations present serious theoretical difficulties, even conceding free competition.
Keywords: 330